Exploring the effects of peripheral sensibility on visuospatial and postural capacities during goal-directed movements in long-term Tai Chi practitioners - Shao, Zhufeng; Li, Li; Mao, Min; Sun, Wei; Zhang, Cui; Song, Qipeng (Frontiers in Aging Neuroscience, 2022)
Background: Falls are directly related to visuospatial ability and postural stability. Perturbations of upper body movements pose a challenge to older adults and may cause falls. This study investigated visuospatial ability and postural stability during goal-directed upper body movements between the Tai Chi and control groups and tried to connect them with their sensations. Methods: Thirty-seven older adults were recruited to perform the touch (TT) and blind touch (BTT) tasks. The target positioning error (TPE), ankle proprioception, tactile sensation, time to stabilization (TTS) and maximum displacement (Dmax) of the center of pressure trajectory were compared between the groups during the tasks. The relationships of visuospatial ability and postural stability to proprioception and tactile sensation were investigated. Results: Dmax in the mediolateral (DmaxML) direction decreased during BTT compared to TT among the Tai Chi group but not the control group. Compared to the control group, less Dmax in the anterio-posterior (DmaxAP) direction, and shorter TTS in AP/ML (TTSAP/TTSML) directions were observed among the Tai Chi group. Compared to TT, DmaxAP decreased during the BTT. The Tai Chi group had less TPE in the vertical (TPEV) direction and in three-dimensional space. Among the Tai Chi group, TPEV, TTSML, and DmaxAP were correlated to their proprioception during plantarflexion; TTSAP was correlated to tactile sensation at the great toe during the TT and BTT; DmaxAP was correlated to tactile sensation at the great toe during the TT. Among the control group, TTSML was correlated to ankle proprioception during dorsiflexion and plantarflexion during the BTT. Conclusion: Long-term Tai Chi practitioners exhibited superior visuospatial ability and postural stability during goal-directed upper body movements, which was associated with sensitive proprioception and tactile sensation.